2012
DOI: 10.1016/j.cherd.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a vane-type pipe separator for oil–water separation

Abstract: An experimental study of a new vane-type pipe separator (VTPS) was conducted for the possible application in the well-bore for oil-water separation and reinjection. Results by using particle image velocimetry (PIV) reveal a better flow field distribution for oil-water separation, which is formed in VTPS than that in hydrocyclone. The effects of split ratio, the oil content, guide vanes' installation and number of guide vanes on oil-water separation performance have been investigated experimentally. Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…By comparison, with the VTPS system the oil phase is concentrated in the central area of the pipe [3]; and both the photographic and the laser image processing techniques are not applicable for DSD measurements because of the graphic overlay problem [2]. Thus, a particle size analyser, Malvern Insitec SX, which is based on light diffraction, was chosen in this study to examine the DSD characteristics in the VTPS.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, with the VTPS system the oil phase is concentrated in the central area of the pipe [3]; and both the photographic and the laser image processing techniques are not applicable for DSD measurements because of the graphic overlay problem [2]. Thus, a particle size analyser, Malvern Insitec SX, which is based on light diffraction, was chosen in this study to examine the DSD characteristics in the VTPS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This methods creates vortical motion in the fluid through rotation of guiding vanes in the pipe center, whereas conventional cyclones for oil-water separation form the vortical motion at the tangential entry structure [2]. The authors have previously demonstrated that this new method can produce improved oil-water separation performance in preliminary experimental study [3]. The feasibility of this method has also been shown at the Caofeidian oil field in West Bohai Bay, China.…”
Section: Introductionmentioning
confidence: 98%
“…As a disadvantage of such separator, it should be noted that the flow inside this kind of separator is highly turbulent and nonstationary, which limits the further application in two-phase flow separation (Hreiz et al, 2014a,b). On the other hand, limited by the space, most of the hydrocyclones and gas-liquid cylindrical cyclones are asymmetrical "single-entry" structures in practical applications, which leads to the asymmetrical internal flow field, and then affects the separation efficiency of the separator (Shi et al, 2012). Compared with the tangential flow cyclone, the flow is put into swirl motion by swirl generators in most of axial cyclones, which results in a relatively low swirl intensity of the fluid (Nieuwstadt and Dirkzwager, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The new vane-type pipe separator uses the guide vanes to produce swirling flow fields to realize centrifugal oil-water separation (Shi et al, 2012;Shi and Xu, 2015). However, the flow characteristics of the swirling flow field are not very clear because of the unique structure of the guide vanes.…”
Section: Introductionmentioning
confidence: 99%